MATHEMATICAL COMMUNICATION OF STUDENTS WITH LOW PERFORMANCE IN MATHEMATICS: GENDER PERSPECTIVE - Pathuddin, Pathuddin; Hasanah, Siti Uswatun; Anggraini, Anggraini (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to describe mathematical communication between male and female students with low mathematical performance and to identify ways to support their mathematical communication skills. Students with mathematical abilities often struggle to express mathematical ideas clearly, making it important to explore their communication patterns and develop effective teaching strategies. A male and a female student from the twelfth grade of high school, were chosen as participants due to their low performance in mathematics. The selection of these subjects was based on the method of pairing data created by Milles. Data collection involved administering tests and using a semi-structured interview approach, which were then analyzed qualitatively. The results of this research indicated that there are differences in mathematical communication exhibited by male and female students. Both participants expressed mathematical concepts by identifying key points obtained from the test. They correctly used mathematical notation and adequately represented their ideas through graphical means. The male student showed a stronger grasp by connecting various concepts. However, there were instances when they struggled to articulate their thoughts accurately in writing. The results of this study provide insights for teachers in designing teaching strategies that improve low-achieving students’ mathematical communication skills, both oral and written communication. This is expected to support students in expressing mathematical ideas effectively.